A Ceramic‐Electrolyte Glucose Fuel Cell for Implantable Electronics. Issue 24 (12th May 2022) - Simons, Philipp; Schenk, Steven A.; Gysel, Marco A.; Olbrich, Lorenz F.; Rupp, Jennifer L. M.
Abstract: Next‐generation implantable devices such as sensors, drug‐delivery systems, and electroceuticals require efficient, reliable, and highly miniaturized power sources. Existing power sources such as the Li–I2 pacemaker battery exhibit limited scale‐down potential without sacrificing capacity, and therefore, alternatives are needed to power miniaturized implants. This work shows that ceramic electrolytes can be used in potentially implantable glucose fuel cells with unprecedented miniaturization. Specifically, a ceramic glucose fuel cell—based on the proton‐conducting electrolyte ceria—that is composed of a freestanding membrane of thickness below 400 nm and fully integrated into silicon for easy integration into bioelectronics is demonstrated. In contrast to polymeric membranes, all materials used are highly temperature stable, making thermal sterilization for implantation trivial. A peak power density of 43 µW cm −2, and an unusually high statistical verification of successful fabrication and electrochemical function across 150 devices for open‐circuit voltage and 12 devices for power density, enabled by a specifically designed testing apparatus and protocol, is demonstrated. The findings demonstrate that ceramic‐based micro‐glucose‐fuel‐cells constitute the smallest potentially implantable power sources to date and are viable options to power the next generation of highly miniaturized implantable medical devices. Abstract : A ceramic‐electrolyte glucose fuel cell as a power source for implantable biomedical devices is introduced and demonstrated. The highly miniaturized device with a thickness below 400 nm exhibits a peak power density of 43 µW cm −2, is fully integrated into silicon, and consists of only ceramic and noble‐metal materials for easy sterilization.